Effectiveness of focused ultrasound for high risk human papillomavirus infection-related cervical lesions. (10th September 2021) - Wang, Wenping; Liu, Yujuan; Pu, Yang; Li, Chengzhi; Zhou, Honggui; Wang, Zhibiao
Abstract: Objective: The purpose of this study was to compare the efficacy of focused ultrasound (FU) and interferon drug therapy for cervical intraepithelial neoplasia 1 (CIN1) and chronic cervicitis associated with high risk human papillomavirus (HR-HPV) infection, as well as analyze the influencing factors. Methods: A retrospective cohort study was performed from January 2017 to December 2019. A total of 592 patients were enrolled, of which 300 patients were treated with FU and 292 patients were treated with interferon drugs. Kaplan-Meier curves and a COX regression model were used to compare the curative effects of the two therapeutic methods using HR-HPV clearance as the main outcome. The relationship between age, HR-HPV infection type, pathological type, preoperative HR-HPV status and HR-HPV clearance were also analyzed. Results: The median time for HR-HPV clearance was 6.00 months (95% CI: 5.24–6.76) in the FU group and 26.00 months (95% CI: 22.32–29.68) in the medication group. A significant difference was observed between the two groups (χ 2 =198.902, p  = 0.000). The HR-HPV clearance rate was 4.927 (95% CI 3.840–6.321; p  = 0.000) times higher in the patients treated with FU than those treated with interferon drugs. In the FU group, no significant difference was observed in HR-HPV clearance rate between CIN1 and chronic cervicitis (χ 2 =0.660, p  = 0.416), which was also insignificant between HR-HPV persistent and non-persistent infections (χ 2 =0.751, p  = 0.386). Conclusion: FU therapy can eliminate HR-HPV infections in a short period of time. Moreover, the treatment efficacy of FU was significantly superior to that of interferon drugs.